Neighbourhood research from a geographical perspective - Drilling, Matthias; Schnur, Olaf (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
The neighbourhood has a very multi-faceted history in geographical research. For a long time, it was the framework for descriptions in Regional Geography and later a normative concept for a ‘better’ society. Today, neighbourhood research has become a laboratory where social problems and their local consequences are identified, analysed and to a certain extent resolved. Essentially, the evolution of geographical neighbourhood research has proceeded in harmony with the development of geography and its epistemological intentions. Thus, the neighbourhood in geography has not been narrowed down to a territorial scale, but rather it is also interpreted as a framework for social interactions, as a place of emotional relationships and, more fundamentally, as a discursively dissolvable category. This article is intended to clarify the contours of neighbourhood research from a geographical perspective in order to foster a further step towards a (critical) reconstruction of the object neighbourhood as an object of study and the discipline of geography in its positioning.